Quantitative impact testing of energy dissipation at surfaces - Constantinides, Georgios; Tweedie, Catherine A.; Savva, Nikos; Smith, James Fielding; Vliet, Krystyn J. Van (My University, 2009)
Impact testing with nanoscale spatial, force, and temporal resolution has been developed to address quantitatively the response of surfaces to impingement of local contact at elevated velocities. Here, an impact is generated by imparting energy to a pendulum carrying an indenter, which then swings towards a specimen surface. The pendulum displacement as a function of time x (t) is recorded, from which one can extract the maximum material penetration x max, residual deformation x r, and indentation durations t in and t out. In an inverse application one can use the x (t) response to extract material constants characterizing the impact deformation and extent of energy absorption, including material specific resistance coefficient C in, coefficient of restitution e, and dynamic hardness H imp. This approach also enables direct access to the ratio H/E, or resilience of the deformed material volume, at impact velocities of interest. The impact response of aluminum was studied for different contact velocities, and the mechanical response was found to correlate well with our one-dimensional contact model. Further experiments on annealed and work hardened gold showed that dynamic hardness H imp scales with contact velocity and highlighted the importance of rate-dependent energy absorption mechanisms that can be captured by the proposed experimental approach.
Keywords: Energy dissipation; Impact; Nanoindentation; Dynamic hardness; Coefficient of restitution